The Evaluation of Otilonium Bromide Treatment in Asian Patients With Irritable Bowel Syndrome - Chang, Full-Young (Korean Society of Neurogastroenterology and Motility, 2011)
BACKGROUND/AIMS: Antispasmodics including otilonium bromide (OB) are recommended to treat irritable bowel syndrome (IBS). However, reports about OB experience in Asia is sparse. The purpose of present study was to provide the efficacy of OB in treating Asian IBS patients. METHODS: Overall, 117 IBS patients meeting Rome II criteria were enrolled in an 8-week, double-blind, active-controlled and single center trial. Randomized participants received either OB 40 mg or mebeverine 100 mg 3 doses daily. The primary endpoints were to evaluate the net changes of abdominal pain/discomfort frequency score (APDFS) and safety profile, while the secondary endpoints were to assess the changes in abdominal pain/discomfort intensity, flatulence, abdominal bloating, satisfied stool frequency etc. RESULTS: Finally, 49 OB and 52 mebeverine subjects were eligible for efficacy analysis. Compared to baselines in per protocol populations, the reduced APDFSs in OB and mebeverine were 0.55 ± 1.20 (P = 0.011) and 0.37 ± 1.11 (P = 0.042), respectively, to show similarly reduced scores. The most reported side effects included dry mouth, nausea and dizziness. Besides, the improved APDFSs at 4th week visit, final alleviations in abdominal pain intensity, flatulence, abdominal bloating and satisfied stool frequency with global assessments filled by both patients and investigators were significantly achieved by both treatments, and OB was not inferior to mebeverine in treating these parameters. CONCLUSIONS: In Orientals, OB is as effective as mebeverine for alleviating IBS symptoms in terms of abdominal pain, flatulence, abdominal bloating etc. However, obvious side effects are also observed. A large-scaled trial and post-marketing surveillance are recommended to confirm its efficacy and safety.